Role of Nitric Oxide in Motor Control: Implications for Parkinson's Disease Pathophysiology and Treatment - Del-Bel, Elaine; Eduardo Padovan-Neto, Fernando; Raisman-Vozari, Rita; Lazzarini, Marcio (Current Pharmaceutical Design, 2011)
According to classical thinking about Parkinson's disease, loss of dopaminergic input from the substantia nigra pars compacta leads to overactivity and underactivity of the indirect and direct output pathways, respectively, in the basal ganglia. Administration of the dopamine precursor L-DOPA (l-3, 4-dihydroxyphenylalanine) is proposed to induce changes in the opposite directions. L-DOPA is the most used drug to treat Parkinson's disease symptoms. After repeated treatment with this compound, however, disabling secondary effects such as the abnormal involuntary movements usually appear. Nitric oxide is a free radical that can also acts as an atypical neurotransmitter and influences dopamine-mediated neurotransmission. In this paper we will briefly review the role of nitric oxide on motor control and in Parkinson's disease, particularly a possible role of nitric oxide in L-DOPA induced dyskinesia in rodents. Recent results show that nitric oxide synthase inhibition reduces L-DOPA-induced dyskinesia in rats and mice. The effect is dose-dependent, does not suffer tolerance nor interferes with L-DOPA positive motor effects. These preclinical findings suggest that nitric oxide is a promising therapeutic target for the reduction of L-DOPA-induced dyskinesia.
Keywords: Motor behaviour